High- Versus Low-Gradient Severe Aortic Stenosis: Demographics, Clinical Outcomes, and Effects of the Initial Aortic Valve Replacement Strategy on Long-Term Prognosis. (May 2017) - Taniguchi, Tomohiko; Morimoto, Takeshi; Shiomi, Hiroki; Ando, Kenji; Kanamori, Norio; Murata, Koichiro; Kitai, Takeshi; Kawase, Yuichi; Izumi, Chisato; Miyake, Makoto; Mitsuoka, Hirokazu; Kato, Masashi; et al.
Abstract : Background—: There is considerable debate on the management of patients with low-gradient severe aortic stenosis (LG-AS), defined as aortic valve area <1 cm 2 with peak aortic jet velocity ⩽4.0 m/s, and mean aortic pressure gradient ⩽40 mm Hg. Methods and Results—: In the CURRENT AS registry (Contemporary Outcomes After Surgery and Medical Treatment in Patients With Severe Aortic Stenosis), there were 2097 patients (initial aortic valve replacement [AVR] strategy: n=977, and conservative strategy: n=1120) with high-gradient severe aortic stenosis (HG-AS) and 1712 patients (initial AVR strategy: n=219, and conservative strategy: n=1493) with LG-AS. AVR was more frequently performed in HG-AS patients than in LG-AS patients (60% versus 28%) during the entire follow-up. In the comparison between the initial AVR and conservative groups, the propensity score–matched cohorts were developed in both HG-AS (n=887 for each group) and LG-AS (n=218 for each group) strata. The initial AVR strategy when compared with the conservative strategy was associated with markedly lower risk for a composite of aortic valve–related death or heart failure hospitalization in both HG-AS and LG-AS strata (hazard ratio, 0.30; 95% confidence interval, 0.25–0.37; P <0.001 and hazard ratio, 0.46; 95% confidence interval, 0.32–0.67; P <0.001, respectively). Among 1358 patients with LG-AS with preserved left ventricular ejection fraction, the initial AVR strategy was associated with a better outcome than the conservative strategy (adjusted hazard ratio, 0.37; 95% confidence interval, 0.23–0.59; P <0.001). Conclusions—: The initial AVR strategy was associated with better outcomes than the conservative strategy in both HG-AS and LG-AS patients, although AVR was less frequently performed in LG-AS patients than in HG-AS patients. The favorable effect of initial AVR strategy was also seen in patients with LG-AS with preserved left ventricular ejection fraction. Clinical Trial Registration—: URL:http://www.umin.ac.jp/ctr/index.htm . Unique identifier: UMIN000012140. Abstract : Supplemental Digital Content is available in the text.